Granzyme B: A Double-Edged Sword in the Response to Influenza Infection in Vaccinated Older Adults - Verschoor, Chris P.; Pawelec, Graham; Haynes, Laura; Loeb, Mark; Andrew, Melissa K.; Kuchel, George A.; McElhaney, Janet E. (Frontiers in Aging, 2021)
Background: Influenza-specific cytolytic T lymphocytes (CTL) have a critical role in clearing the virus from the lungs, but are poorly stimulated by current inactivated influenza vaccines. Our previous work suggests that granzyme B (GrB) activity predicts protection against laboratory-confirmed influenza infection (LCII) in older adults. However, basal GrB (bGrB) activity increases with age and the frequency of GrB+ CTL that do not co-express perforin increases following influenza infection, thereby acting as a potential contributor to immune pathology. Objectives: Using data from a 4-year randomized trial of standard- versus high-dose influenza vaccination, we sought to determine whether measurements of GrB activity alone indicate a protective vs. pathologic response to influenza infection. We compared LCII to No-LCII subsets according to: pre-vaccination bGrB activity; and induced GrB activity in ex vivo influenza-challenged peripheral blood mononuclear cells (PBMC) at 4- and 20-weeks post-vaccination. Results: Over four influenza seasons (2014-2018), 27 of 608 adult participants aged 65 years and older developed influenza A/H3N2-LCII (n=18) or B-LCII (n=9). Pre-vaccination, there was a significant correlation between bGrB and ex vivo GrB activity in each of the H3N2-LCII, B-LCII, and No-LCII subsets. Although pre-vaccination ex vivo GrB activity was significantly higher in B-LCII vs. No-LCII with a trend for H3N2-LCII vs. No-LCII, there was no difference in the response to vaccination. In contrast, there was a trend toward increased pre-vaccination bGrB activity and LCII: Odds Ratio (OR) (95% confidence intervals) OR = 1.46 (0.94, 2.33). By 20-weeks post-vaccination, there were significant fold-increases in ex vivo GrB activity specific for the infecting subtype in H3N2-LCII: OR = 1.63 (1.35, 2.00) and B-LCII: OR = 1.73 (1.34, 2.23). Conclusions: Our results suggest that the poor GrB responses to influenza vaccination that led to development of LCII can be attributed to inactivated formulations rather than the aging immune system since LCII cases generated robust ex vivo GrB responses following natural infection. Further, we identified bGrB as a biomarker of those who remain at risk for LCII following vaccination. Future studies will focus on understanding the mechanisms responsible for the shift in GrB-mediated protection vs. potential immune pathology caused by GrB release.